FERONIA Confers Resistance to Photooxidative Stress in Arabidopsis - Shin, Seung Yong; Park, Ji-Sun; Park, Hye-Bin; Moon, Ki-Beom; Kim, Hyun-Soon; Jeon, Jae-Heung; Cho, Hye Sun; Lee, Hyo-Jun (Frontiers in Plant Science, 2021)
Plants absorb light energy required for photosynthesis, but excess light can damage plant cells. To protect themselves, plants have developed diverse signaling pathways which are activated under high-intensity light. Plant photoprotection mechanisms have been mainly investigated under conditions of extremely high amount of light; thus, it is largely unknown how plants manage photooxidative damage under moderate light intensities. In the present study, we found that FERONIA (FER) is a key protein that confers resistance to photooxidative stress in plants under moderate light intensity. FER-deficient mutants were highly susceptible to increasing light intensity and exhibited photobleaching even under moderately elevated light intensity (ML). Light-induced expression of stress genes was largely diminished by the fer-4 mutation. In addition, excitation pressure on Photosystem II was significantly increased in fer-4 mutants under ML. Consistently, reactive oxygen species, particularly singlet oxygen, accumulated in fer-4 mutants grown under ML. FER protein abundance was found to be elevated after exposure to ML, which is indirectly affected by the ubiquitin-proteasome pathway. Altogether, our findings showed that plants require FER-mediated photoprotection to maintain their photosystems even under moderate light intensity.